“DISEÑO DE UN TABLERO DE TRANSFERENCIA PARA LA REPETIDORA EL PAILON DE LA CNT. E.P.” - MURILLO MINDIOLA, JONATHAN IVAN (2018)
The National Telecommunications Corporation CNT EP is a company dedicated to the supply and marketing of telecommunications services (fixed telephony, mobile telephony, internet, data service, satellite television, etc.) for which it has a vast network interconnected by all of Ecuador, thus generating the reliability that every customer wants to have at the time of acquiring a service, whether at home or at the company level, thus maintaining the trust of its users. The transmission methods most used by the CNT E.P are physical by means of a fiber optic backbone and aerial by means of a point-to-point radio link. The production of the fundamental services provided by the CNT E.P are generated by fixed access platforms called nodes or exchanges, mobile access platforms known as Nodes B and by satellite systems for the DTH service (satellite television). The company that provides the commercial electric service in each of the facilities of the CNT E.P is the National Electricity Corporation CNEL EP.